A weather-resistant, air-permeable composite based on a microporous membrane

CN122978627APending Publication Date: 2026-10-27GUANGDONG CHAOWEI NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611173571.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-04
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0004]本发明的目的在于提供一种基于微孔透膜的耐候透气复合材料,以解决现有传统透气防护材料在面对环境温湿度变化时,透气性能难以主动调节以及受损后难以可逆修复的问题;为此,本发明提供了一种能够不依赖多层层压结构、在单一膜体内同时具备温度响应、湿度响应、梯度孔结构、液态水阻隔及具有动态自修复能力的温湿刺激响应型透气多孔膜

Benefits of technology

[0013]本发明的有益效果在于:温敏响应、湿敏响应、梯度孔结构、液态水阻隔、透气调节和动态修复功能均集成于同一膜体内部,不依赖传统多层层压结构,能够降低由层间热膨胀和吸湿溶胀不匹配引起的剥离风险;

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application relates to the field of high molecular porous membrane and stimulus response high molecular material, specifically to a weather-resistant and breathable composite material based on microporous membrane; the microporous membrane has a gradient connected microporous structure, the pore wall of the microporous membrane is interpenetrated with a temperature-sensitive first crosslinked network, a humidity-sensitive second crosslinked network and a dynamic disulfide bond structure; the material combines gas phase and liquid phase non-solvent induced phase separation to construct an asymmetric pore size distribution, and utilizes different polymer segments to respond to temperature and humidity changes; the core is to synergistically regulate the water content of the pore wall and the pore throat size in the single membrane body through the interpenetrating double network, actively control the gas mass transfer resistance, and realize the reversible self-repair of micro-cracks by relying on the dynamic exchange of the disulfide bond; the present application does not use the traditional multilayer laminated structure, solves the peeling defect caused by the mismatch of thermal expansion and hygroscopic swelling between layers, integrates the temperature and humidity double response, gas regulation, liquid water barrier and dynamic repair functions in the single layer membrane, and improves the comprehensive weather resistance of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the fields of porous polymer membranes, stimulus-responsive polymer materials, and functional protective materials, specifically a weather-resistant and breathable composite material based on a microporous membrane. Background Technology

[0002] Applications such as outdoor protection, medical dressings, sportswear, and special industrial protection typically require materials to simultaneously possess the characteristics of preventing liquid water penetration, allowing sweat or water vapor to escape, environmental adaptability, and long-term durability; traditional breathable protective materials mainly include microporous membranes, hydrophilic dense membranes, and multilayer composite membranes.

[0003] Microporous membranes mainly rely on fixed pore size and fixed porosity to achieve water vapor transport, and their air permeability usually cannot be actively adjusted with changes in temperature and humidity. Hydrophilic dense membranes can transport water vapor through the dissolution-diffusion mechanism of water molecules, but they are prone to moisture absorption and swelling in high humidity environments, resulting in a decrease in moisture permeability. Multilayer composite membranes achieve comprehensive performance by laminating or bonding waterproof layers, moisture permeable layers, support layers, and functional coatings. However, there are differences in the coefficient of thermal expansion, moisture absorption and swelling rate, and elastic modulus between different layers. During long-term temperature and humidity cycles, mechanical bending, or washing, interfacial stress is easily generated, which can lead to delamination, blistering, or peeling. Furthermore, most existing temperature-sensitive breathable materials rely solely on the volume phase transition of a single temperature-sensitive segment, and the impact of humidity changes on their breathability is not effectively controlled; some materials with unidirectional moisture-wicking function rely on fixed conical pores, gradient wetting pores, or surface coatings, and once the pore structure and surface energy are formed, it is difficult to dynamically adjust them according to environmental conditions; existing materials also generally lack reversible repair capabilities after damage, and microcracks can easily cause irreversible degradation of liquid water barrier performance and mechanical properties. Therefore, it is necessary to develop a stimulus-responsive, breathable porous membrane that does not rely on a multilayer lamination structure and simultaneously possesses temperature response, humidity response, gradient pore structure, liquid water barrier, and a certain degree of self-healing ability within a single membrane. Summary of the Invention

[0004] The purpose of this invention is to provide a weather-resistant and breathable composite material based on a microporous membrane, to solve the problems of existing traditional breathable protective materials, which are difficult to actively adjust their breathability and are difficult to reversibly repair after damage when faced with changes in environmental temperature and humidity. To this end, this invention provides a temperature and humidity responsive breathable porous membrane that can simultaneously possess temperature response, humidity response, gradient pore structure, liquid water barrier, and dynamic self-healing capabilities within a single membrane without relying on a multi-layer lamination structure. The specific technical solution is as follows: A weather-resistant and breathable composite material based on a microporous membrane includes a microporous membrane with a gradient interconnected microporous structure. The pore walls of the microporous membrane include a first cross-linked polymer network, a second cross-linked polymer network interpenetrating in the first cross-linked polymer network, and a dynamic disulfide bond structure distributed in the first cross-linked polymer network. The first crosslinked polymer network is formed by polymerization of N-isopropylacrylamide, a hydrophobic modifier monomer, and N,N-bisacryloylcysteine, wherein the hydrophobic modifier monomer is selected from one or more of octadecyl methacrylate, perfluorohexyl ethyl acrylate, and perfluorobutyl ethyl acrylate; The second crosslinked polymer network is formed by polymerizing polyethylene glycol methyl ether acrylate and a second network crosslinking agent, wherein the second network crosslinking agent is selected from one or more of polyethylene glycol diacrylate, polyethylene glycol dimethacrylate and polypropylene glycol diacrylate; the average pore size on the substrate contact side of the gradient interconnected microporous structure is 20-100 μm, and the average pore size on the gas phase contact side is 1-10 μm.

[0005] Preferably, based on a total of 100 moles of polymerizable double-bonded monomers, the reaction components of the first and second crosslinked polymer networks include: 60-80 moles of N-isopropylacrylamide, 3-15 moles of hydrophobic regulating monomer, 2-8 moles of N,N-bisacryloylcysteine, 10-30 moles of polyethylene glycol methyl ether acrylate, and 1-8 moles of the second network crosslinking agent.

[0006] Preferably, the number average molecular weight of the polyethylene glycol methyl ether acrylate is 300-1000; the amount of the second network crosslinking agent is 2-8% of the molar number of polyethylene glycol methyl ether acrylate.

[0007] Preferably, the first crosslinked polymer network further includes a sulfur-containing auxiliary monomer, which is selected from one or more of 2-mercaptoethyl acrylate and 2-mercaptoethyl methacrylate, and its amount is 0.2-3 moles of the total number of polymerizable double bond monomers.

[0008] Preferably, the first crosslinked polymer network further includes 1′-(2-acryloyloxyethyl)-3′,3′-dimethyl-6-nitrospiro[benzopyran-2,2′-indole] or 1′-(2-methacryloyloxyethyl)-3′,3′-dimethyl-6-nitrospiro[benzopyran-2,2′-indole], wherein the amount of 1′-(2-acryloyloxyethyl)-3′,3′-dimethyl-6-nitrospiro[benzopyran-2,2′-indole] or 1′-(2-methacryloyloxyethyl)-3′,3′-dimethyl-6-nitrospiro[benzopyran-2,2′-indole] is 0.05-1 molar part of the total molar number of all polymerizable double-bonded monomers.

[0009] Preferably, the pore structure of the microporous membrane is a conical pore, a truncated conical pore, a funnel-shaped pore, a gradient throat structure, or a combination thereof; the average pore diameter on the substrate contact side is 30-80 μm, and the average pore diameter on the gas phase contact side is 2-8 μm.

[0010] Preferably, the microporous membrane further includes a porogen selected from one or more of polyvinylpyrrolidone, polyethylene glycol, polyvinyl alcohol, and polyacrylic acid; the amount of the porogen is 5-30 wt% based on the total mass of polymerizable monomers of the first crosslinked polymer network.

[0011] Preferably, the pore-forming agent is polyvinylpyrrolidone, and the weight-average molecular weight of the polyvinylpyrrolidone is 10,000-100,000; the mass ratio of the first crosslinked polymer network to the second crosslinked polymer network is 75:25 to 95:5.

[0012] Preferably, the first cross-linked polymer network and the second cross-linked polymer network form an interpenetrating structure through one or more of the following: covalent bonding, segment entanglement, hydrogen bonding, and polar interaction.

[0013] The beneficial effects of this invention are as follows: temperature-sensitive response, humidity-sensitive response, gradient pore structure, liquid water barrier, air permeability regulation and dynamic repair functions are all integrated inside the same membrane, without relying on traditional multilayer lamination structure, which can reduce the risk of peeling caused by the mismatch between interlayer thermal expansion and moisture absorption swelling. The N-isopropylacrylamide segments undergo a reversible volumetric phase transition to impart thermosensitive properties to the membrane, while the polyethylene glycol methyl ether acrylate network undergoes hygroscopic swelling to achieve humidity response. Through the joint regulation of pore wall water content, pore throat size, and gas mass transfer resistance by two interwoven networks, the material can adapt to different temperature and humidity environments. An asymmetric pore size distribution is formed in the membrane thickness direction, providing a structural basis for liquid water barrier and water vapor transport. Detailed Implementation

[0014] The technical solutions in the embodiments of the present invention will be clearly and completely described below; the described embodiments are some embodiments of the present invention, but not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0015] Example 1: This embodiment provides an intrinsically temperature and humidity dual-response stimulus-responsive breathable porous membrane, specifically including the following steps: S1. Preparation of the first network casting solution: Weigh 75 mmol of N-isopropylacrylamide, 6 mmol of perfluorohexyl ethyl acrylate, 4 mmol of N,N-bisacryloylcysteine, 1 mmol of 2-mercaptoethyl acrylate, 0.2 mmol of spiropyran acrylate, 0.15 g of photoinitiator 2959, and 12 g of polyvinylpyrrolidone; add the above components to 60 mL of N,N-dimethylformamide, stir for 18 h under nitrogen protection and light protection to obtain a homogeneous casting solution, and degas under reduced pressure for 20 min at a degassing pressure of -0.08 MPa; The spiropyran acrylate is 1′-(2-acryloyloxyethyl)-3′,3′-dimethyl-6-nitrospiro[benzopyran-2,2′-indole], with a purity of not less than 98%, and is an analytical grade reagent. This monomer can also be prepared by esterification of 6-nitrospiropyran hydroxyethyl derivative with acryloyl chloride in the presence of triethylamine and 4-dimethylaminopyridine, followed by column chromatography purification. The amount of Irgacure 2959 used is 1.2 wt% of the total mass of the first network polymerizable monomers. S2. Coating and Pregelation: The casting solution is coated onto the glass substrate with a wet film thickness of 220 μm. After coating, the film is exposed to an environment of 25°C and 90% relative humidity for 3 min. Under nitrogen protection, the film is pre-irradiated with 365 nm ultraviolet light for 30 s to induce partial gelation of the film. S3. Gas-phase induced phase separation: The pre-gelled wet membrane is subjected to gas-phase induced phase separation. The gas phase ambient temperature is 25℃, the relative humidity is 90%, and the exposure time is 3min. S4. Liquid-phase non-solvent-induced phase separation: Immerse the membrane and substrate together in a 15°C coagulation bath of deionized water and isopropanol, with a volume ratio of deionized water to isopropanol of 8:2, for 20 min. S5. First network fully cured: The phase-separated membrane is placed in a nitrogen-protected environment and irradiated with 365nm ultraviolet light for 15 minutes at an intensity of 12mW / cm² to allow the first network to fully polymerize and crosslink. The acrylamide groups at both ends of N,N-bisacryloylcysteine ​​participate in free radical polymerization, and the disulfide bonds in its molecule remain in the first crosslinked polymer network as crosslinking bridges connecting the two polymer segments. The acrylate groups in 2-mercaptoethyl acrylate participate in polymerization, and some thiol groups remain in the network as side groups. S6. Second Moisture-Sensitive Network Impregnation and Curing: A second network precursor solution was prepared by mixing polyethylene glycol methyl ether acrylate, polyethylene glycol diacrylate, Irgacure 2959, and deionized water with ethanol as a mixed solvent, wherein the mass ratio of polyethylene glycol methyl ether acrylate to polyethylene glycol diacrylate was 91.6:8.4, and the total concentration of polymerizable components was 8 wt%. Specifically, 7.50g of polyethylene glycol methyl ether acrylate and 0.69g of polyethylene glycol diacrylate were weighed, and 0.06g of Irgacure 2959 was added. The total mass was then made up to 102.9g with a mixed solvent of deionized water and ethanol in a mass ratio of 1:1, with 47.325g of deionized water and 47.325g of ethanol. The first network membrane was immersed in the precursor solution and vacuum-wetted for 20min at -0.06MPa. After removal, excess precursor solution was removed from the surface. The total mass of precursor solution absorbed by a single membrane was set to 47.50g, and the measured absorption amount of the polymerizable component of the second network was set to 3.78g. The second humidity-sensitive network was formed by irradiating with 365nm ultraviolet light for 12 minutes under nitrogen protection. Based on the total number of polymerizable double bonds, the molar numbers of polymerizable double bonds corresponding to N-isopropylacrylamide, perfluorohexyl ethyl acrylate, N,N-bisacryloylcysteine, 2-mercaptoethyl acrylate, spiropyran acrylate, polyethylene glycol methyl ether acrylate, and polyethylene glycol diacrylate in this embodiment were 75 mmol, 6 mmol, 8 mmol, 1 mmol, 0.2 mmol, 15 mmol, and 2.4 mmol, respectively, with a total of 107.6 mmol of polymerizable double bonds. The mixture contains 13.94 moles of polyethylene glycol methyl ether acrylate and 2.23 moles of polyethylene glycol diacrylate. The molar ratio of the two based on the number of monomer molecules is 92.6:7.4, and the ratio based on the number of polymerizable double bonds is 86.2:13.8. After impregnation, the total amount of precursor liquid absorbed is determined by weighing the difference in mass of the film before and after impregnation, and the amount of polymerizable component absorbed by the second network is calculated by combining the mass fraction of polymerizable components in the precursor liquid. In this embodiment, the total amount of precursor liquid absorbed is controlled within the range of 45.0-50.0g, and the corresponding amount of polymerizable component absorbed by the second network is controlled within the range of 3.6-4.0g. During the curing process, the thiol groups retained in the first network undergo thiol-disulfide bond exchange with the disulfide bonds on the adjacent chain segments, allowing the disulfide bond connection positions to be redistributed in the network. This exchange mainly occurs after the membrane absorbs moisture and can occur under the recovery treatment conditions of 60°C and 80% relative humidity without the need for additional oxidant. The disulfide bond exchange and the covalent cross-linked structure of the first network together constitute a reconfigurable dynamic connection. S7. Washing, solvent replacement and drying: The cured film is peeled off from the substrate and washed sequentially with 60℃ deionized water and 50% ethanol aqueous solution for 48h, with the washing solution being changed every 8h; the ethanol is replaced with deionized water, and then a second replacement is performed with tert-butanol; the film is then freeze-dried at -80℃ for 24h to obtain an intrinsic temperature and humidity dual-response stimulus-responsive breathable porous membrane. The measured film thickness after freeze-drying was set at 60 μm, with an allowable deviation of ±5 μm. The drying endpoint was determined by constant weight method, with a mass change rate of less than 0.1% between two consecutive weighings 6 hours apart. The residual organic solvent in the membrane was detected by gas chromatography, with a total residual amount of less than 0.5 wt%. After drying, the network mass was determined by selective dissolution combined with weighing method: first, a solvent capable of dissolving the second network but not the first network was used for selective dissolution, and the resulting first network portion was filtered and dried to constant weight. The dry basis mass of the first network is simultaneously checked by material balance calculation based on the sum of the measured feed masses of each polymerizable monomer in the first network. Polyvinylpyrrolidone, unreacted monomers, initiators, washing solvents, and other soluble residues are not included in the mass of the first network. The mass of the second network is determined based on the amount of polymerizable components absorbed by the second network after impregnation and the constant weight result after curing. In this embodiment, the dry basis mass of the first network was measured to be 12.1 g, the dry basis mass of the second network was 3.8 g, and the mass ratio of the first network to the second network was 76:24.

[0016] Example 2: This embodiment provides an intrinsically temperature and humidity dual-response stimulus-responsive breathable porous membrane, specifically including the following steps: S1. Preparation of the first network casting solution: Weigh 60 mmol of N-isopropylacrylamide, 3 mmol of octadecyl methacrylate, 2 mmol of N,N-bisacryloylcysteine, 0.2 mmol of 2-mercaptoethyl acrylate, 0.10 g of Irgacure 2959, and 8 g of polyvinylpyrrolidone; add the above components to 50 mL of N,N-dimethylformamide, stir for 16 h under nitrogen protection and in the dark, degas for 15 min, and the degassing pressure is -0.07 MPa; S2. Splicing and pregelation: The casting solution was sprayed onto a polyethylene terephthalate substrate with a wet film thickness of 150 μm; after spraying, the film was exposed to an environment of 20°C and 85% relative humidity for 2 min; and then pre-irradiated with 365 nm ultraviolet light for 20 s. S3. Gas-phase induced phase separation: Expose the wet membrane to a gas-phase environment at 20℃ and 85% relative humidity for 2 minutes; S4. Liquid-phase non-solvent-induced phase separation: Immerse the membrane in a 10℃ coagulation bath of deionized water and isopropanol, with a volume ratio of deionized water to isopropanol of 9:1, for 15 min. S5. First network fully cured: Irradiated with 365nm ultraviolet light for 12 minutes under nitrogen protection, with an ultraviolet light intensity of 10mW / cm². S6. Second moisture-sensitive network impregnation and curing: Polyethylene glycol methyl ether acrylate, polyethylene glycol diacrylate and Irgacure 2959 with a number average molecular weight of 400 are dissolved in a mixed solvent of water and ethanol to prepare a precursor solution with a total polymerizable component concentration of 5wt%. Specifically, 6.00 g of polyethylene glycol methyl ether acrylate, 0.46 g of polyethylene glycol diacrylate, and 0.05 g of Irgacure 2959 were weighed out and added to 61.345 g of deionized water and 61.345 g of ethanol to obtain a precursor solution with a total mass of 129.20 g. The mass ratio of polyethylene glycol methyl ether acrylate to polyethylene glycol diacrylate was 92.9:7.1, and the amount of polyethylene glycol diacrylate used was 5.3 mol% of the molar amount of polyethylene glycol methyl ether acrylate. After vacuum impregnating the first network membrane at -0.03 MPa for 15 min, it was removed and excess precursor liquid was removed from the membrane surface. It was then cured by irradiation with 365 nm ultraviolet light for 8 min. The total amount of precursor liquid absorbed was determined by weighing the membrane before and after impregnation. The measured amount of polymerizable component absorbed by the second network was calculated based on the mass fraction of polymerizable component in the precursor liquid. The total amount of precursor liquid absorbed by a single membrane was controlled to be 56-64 g, corresponding to a measured amount of polymerizable component absorbed of 2.8-3.2 g. S7. Washing, solvent replacement and drying: The membrane was washed with deionized water and 30% ethanol aqueous solution for 36 h, then replaced with tert-butanol and freeze-dried to obtain a porous membrane.

[0017] Example 3: This embodiment provides an intrinsically temperature and humidity dual-response stimulus-responsive breathable porous membrane, specifically including the following steps: S1. Preparation of the first network casting solution: Weigh 70 mmol of N-isopropylacrylamide, 8 mmol of perfluorobutyl ethyl acrylate, 5 mmol of N,N-bisacryloylcysteine, 1.5 mmol of 2-mercaptoethyl methacrylate, 0.5 mmol of spiropyran methacrylate, 0.12 g of Irgacure 2959, and 10 g of polyvinylpyrrolidone; add 55 mL of N,N-dimethylformamide, and stir for 18 h under nitrogen protection and in the dark, followed by degassing for 20 min at a degassing pressure of -0.08 MPa; The spiropyran methacrylate is 1′-(2-methacryloyloxyethyl)-3′,3′-dimethyl-6-nitrospiro[benzopyran-2,2′-indole], with a purity of not less than 98%. Its preparation method involves esterifying the corresponding 6-nitrospiropyran hydroxyethyl derivative with methacryloyl chloride in the presence of triethylamine and 4-dimethylaminopyridine, followed by purification by column chromatography. The amount of Irgacure 2959 used is 1.0 wt% of the total mass of the first network polymerizable monomers. S2. Scraping and pre-gelling: The casting solution is scraped onto the glass substrate, and the wet film thickness is 250μm; after scraping, it is exposed to an environment of 28℃ and 92% relative humidity for 4min, and then pre-irradiated with 365nm ultraviolet light for 40s. S3. Gas-phase induced phase separation: Expose the wet membrane to a gas-phase environment at 28℃ and 92% relative humidity for 4 min; S4. Liquid-phase non-solvent-induced phase separation: Immerse the membrane in a 12℃ coagulation bath of deionized water and isopropanol, with a volume ratio of deionized water to isopropanol of 8:2, for 25 min. S5. First network fully cured: Irradiated with 365nm ultraviolet light for 18 minutes under nitrogen protection, with an ultraviolet light intensity of 15mW / cm². S6. Second moisture-sensitive network impregnation and curing: Polyethylene glycol methyl ether acrylate, polyethylene glycol dimethacrylate and Irgacure 2959 with a number average molecular weight of 500 are dissolved in a mixed solvent of water and ethanol to prepare a precursor solution with a total polymerizable component concentration of 10wt%. Specifically, 7.50 g of polyethylene glycol methyl ether acrylate, 0.63 g of polyethylene glycol dimethacrylate, and 0.06 g of Irgacure 2959 were weighed out, and 36.555 g of deionized water and 36.555 g of ethanol were added to obtain a precursor solution with a total mass of 81.30 g. The mass ratio of polyethylene glycol methyl ether acrylate to polyethylene glycol dimethacrylate was 92.3:7.7, and the amount of polyethylene glycol dimethacrylate used was 7.3 mol% of the molar amount of polyethylene glycol methyl ether acrylate. After the first network membrane was vacuum-impregnated at -0.06MPa for 25 minutes, it was removed and excess precursor liquid was removed from the membrane surface. The total mass of precursor liquid absorbed by a single membrane was set to 40.00g, and the corresponding amount of polymerizable component absorbed by the second network was set to 4.00g. The membrane was then cured by irradiation with 365nm ultraviolet light for 12 minutes. Based on the total number of polymerizable double bonds, in this example, the molar numbers of polymerizable double bonds corresponding to N-isopropylacrylamide, perfluorobutyl ethyl acrylate, N,N-bisacryloylcysteine, 2-mercaptoethyl methacrylate, spiropyran methacrylate, polyethylene glycol methyl ether acrylate, and polyethylene glycol dimethacrylate are 70 mmol, 8 mmol, 10 mmol, 1.5 mmol, 0.5 mmol, 15 mmol, and 2.2 mmol, respectively, with a total of 107.2 mmol of polymerizable double bonds. In this embodiment, polyethylene glycol methyl ether acrylate accounts for 13.99 moles and polyethylene glycol dimethacrylate accounts for 2.05 moles. The molar ratio of the two based on the number of monomer molecules is 93.2:6.8, and the ratio based on the number of polymerizable double bonds is 87.2:12.8. The total amount of precursor liquid absorbed before and after impregnation is determined by weighing the difference in mass of the membrane. The measured amount of polymerizable component absorbed by the second network is calculated based on the mass fraction of polymerizable component in the precursor liquid. In actual production, the aforementioned 40.00g and 4.00g are used as the set values ​​for this embodiment, and the allowable process control ranges are 38-42g and 3.8-4.2g, respectively. S7. Washing, solvent replacement and drying: The membrane was washed with deionized water and 50% ethanol aqueous solution for 48 h, replaced with tert-butanol and then freeze-dried to obtain a porous membrane; the measured membrane thickness after freeze-drying was set at 65 μm, and the allowable deviation of the membrane thickness was ±5 μm; the mass change rate between two consecutive weighings with an interval of 6 h was less than 0.1%, and the residual organic solvent in the membrane was detected by gas chromatography, with the total residual amount being less than 0.5 wt%.

[0018] Example 4: This embodiment provides an intrinsically temperature and humidity dual-response stimulus-responsive breathable porous membrane, specifically including the following steps: S1. Preparation of the first network casting solution: Weigh 80 mmol of N-isopropylacrylamide, 15 mmol of octadecyl methacrylate, 8 mmol of N,N-bisacryloylcysteine, 3 mmol of 2-mercaptoethyl acrylate, 1 mmol of spiropyran acrylate, 0.18 g of Irgacure 2959, and 15 g of polyvinylpyrrolidone; add 70 mL of N,N-dimethylformamide, and stir for 20 h under nitrogen protection and in the dark, then degas for 25 min at a degassing pressure of -0.09 MPa; S2. Scraping and pre-gelling: The casting solution was scraped onto a stainless steel strip substrate with a wet film thickness of 300 μm; after scraping, it was exposed to an environment of 35°C and 95% relative humidity for 5 min, and then pre-irradiated with 365nm ultraviolet light for 60 s. S3. Gas-phase induced phase separation: Expose the wet membrane to a gas-phase environment at 35℃ and 95% relative humidity for 5 minutes; S4. Liquid-phase non-solvent induced phase separation: Immerse the membrane in a coagulation bath of deionized water and isopropanol at 18°C, with a volume ratio of deionized water to isopropanol of 7:3, for 30 min. S5. First network fully cured: Irradiated with 365nm ultraviolet light for 20 minutes under nitrogen protection, with an ultraviolet light intensity of 18mW / cm². S6. Second moisture-sensitive network impregnation and curing: Polyethylene glycol methyl ether acrylate, polypropylene glycol diacrylate and Irgacure 2959 with a number average molecular weight of 600 are dissolved in a mixed solvent of water and isopropanol to prepare a precursor solution with a total polymerizable component concentration of 12wt%. Specifically, 9.00 g of polyethylene glycol methyl ether acrylate, 0.52 g of polypropylene glycol diacrylate, and 0.06 g of Irgacure 2959 were weighed out, and 34.865 g of deionized water and 34.865 g of isopropanol were added to obtain a precursor solution with a total mass of 79.31 g. The mass ratio of deionized water to isopropanol was 1:1, the mass ratio of polyethylene glycol methyl ether acrylate to polypropylene glycol diacrylate was 94.5:5.5, and the amount of polypropylene glycol diacrylate was 6.0 mol% of the molar amount of polyethylene glycol methyl ether acrylate. The total mass of the polymerizable component was 9.52 g, accounting for 12.00 wt% of the total mass of the precursor solution. The first network membrane was vacuum-impregnated at -0.08 MPa for 30 min; after removal, excess precursor liquid was removed from the membrane surface. The total mass of precursor liquid absorbed by a single membrane was set to 39.66 g, and the corresponding absorbed amount of polymerizable component of the second network was set to 4.76 g; the second moisture-sensitive network was cured by irradiation with 365 nm ultraviolet light for 15 min. In the first network, the two acrylamide groups of N,N-bisacrylcysteine ​​participate in the polymerization of the first network, and its disulfide bond is located between the crosslinking points and is retained as a dynamic disulfide bond; the acrylate group of 2-mercaptoethyl acrylate participates in the polymerization, and the thiol part is retained on the polymer chain segment; after the membrane absorbs moisture, the retained thiol group performs nucleophilic attack on the adjacent disulfide bond under the conditions of 60°C and 80% relative humidity, resulting in thiol-disulfide bond exchange, which causes the crosslinking points to undergo reversible recombination, thereby realizing the restoration of network connection in the damaged area; S7. Washing, solvent replacement and drying: The membrane was washed with deionized water and 50% ethanol aqueous solution for 60 h, replaced with tert-butanol and then freeze-dried to obtain a porous membrane.

[0019] Comparative Example 1: The difference between this comparative example and Example 1 is that the gas-phase induced phase separation in step S3 is omitted, while the remaining operation steps and process parameters are exactly the same as in Example 1; the membrane of this comparative example directly enters the liquid-phase non-solvent induced phase separation and subsequent curing process.

[0020] Comparative Example 2: The difference between this comparative example and Example 1 is that the second moisture-sensitive network impregnation and curing in step S6 is omitted, while the remaining operation steps and process parameters are exactly the same as in Example 1; this comparative example only retains the first crosslinked polymer network and dynamic disulfide bond structure.

[0021] Comparative Example 3: The difference between this comparative example and Example 1 is that N,N-bisacrylcysteine ​​is replaced with an equimolar amount of polyethylene glycol diacrylate, while the remaining operating steps and process parameters are exactly the same as in Example 1; dynamic disulfide bond structures are no longer introduced in this comparative example.

[0022] Comparative Example 4: The difference between this comparative example and Example 1 is that the polyvinylpyrrolidone pore-forming agent is omitted when preparing the first network casting solution, while the remaining operation steps and process parameters are exactly the same as in Example 1; this comparative example is still coated, phase separated, cured, impregnated and dried according to Example 1.

[0023] Comparative Example 5: The difference between this comparative example and Example 1 is that the volume ratio of deionized water to isopropanol coagulation bath in step S4 is adjusted from 8:2 to 10:0, while the remaining operation steps and process parameters are exactly the same as in Example 1; this comparative example still retains the gas-induced phase separation, sequential photocuring and second network construction process.

[0024] Performance Tests and Data Sheets: Molecular weight testing: The number-average molecular weight of polyethylene glycol methyl ether acrylate and the weight-average molecular weight of polyvinylpyrrolidone were determined by gel permeation chromatography; water vapor transmission rate was tested according to the equivalent method of ASTM E96, using the desiccant cup method, with an effective sample area of ​​50 cm², and the sample film thickness was recorded as the average thickness after freeze-drying. The test temperatures were 20℃ and 38℃, the relative humidity was controlled at 40% and 80%, the air velocity outside the cup was 0.3 m / s, and the samples were weighed every 24 hours for 24 consecutive hours. The average value of 3 parallel samples was taken. The hydrostatic pressure was tested according to AATCC 127. The effective area of ​​the sample was 100 cm². The water pressure was continuously increased at a rate of 10 kPa / min. The hydrostatic pressure was taken as the pressure at which three consecutive drops of water seeped from the sample. The average value of three parallel samples was taken. The tensile properties were tested according to ISO 527-3. The sample was cut into strips with a length of 100 mm and a width of 15 mm. The tensile speed was 50 mm / min. A 10mm long and 0.5mm wide through-scratches were prepared in the center of the sample along the transverse direction, with the scratch depth reaching the film thickness. The sample was then subjected to a recovery treatment at 60℃ and 80% relative humidity for 24 hours. The tensile strength recovery rate was calculated using the following formula: Tensile strength recovery rate (%) = (Recovered tensile strength - Tensile strength after scratch) / (Initial tensile strength without scratch - Tensile strength after scratch) × 100%. Five parallel samples were tested in each group, and the average value was taken. The pore size distribution was statistically analyzed using scanning electron microscopy. At least five fields of view were randomly selected on both the gas phase contact side and the substrate contact side, and at least 50 pores were counted in each field of view. The arithmetic mean was then taken. To verify the weather resistance, the films obtained in Examples 1-4 were subjected to UV aging, damp heat aging, temperature cycling, and outdoor exposure tests, respectively. UV aging was performed using a UVA-340 UV aging chamber with an irradiance of 0.89 W / m² (340 nm). One cycle consisted of 8 hours of irradiation at 60°C followed by 4 hours of condensation at 50°C, for a total of 500 hours. Damp heat aging was conducted at 85°C and 85% relative humidity for 240 hours. The temperature cycling conditions were -20℃ for 1 hour and 60℃ for 1 hour, with a heating and cooling rate of 5℃ / min, for a total of 50 cycles; the outdoor exposure test was conducted in a natural environment for 30 days; before and after aging, the water vapor transmission rate, hydrostatic pressure and tensile strength recovery rate were tested according to the above method, and the performance retention rate was calculated by the ratio of the values ​​after aging to the values ​​before aging. In Examples 1-4, after 500 hours of UV aging, the water vapor transmission rate remained at 91%-95%, the hydrostatic pressure remained at 88%-93%, and the tensile strength recovery rate remained at 90%-94%; after 240 hours of damp heat aging, the rates were 89%-94%, 87%-92%, and 88%-93%, respectively; after 50 temperature cycles, the rates were 92%-96%, 90%-94%, and 91%-95%, respectively; and after 30 days of outdoor exposure, the rates were 86%-92%, 84%-90%, and 85%-91%, respectively. Table 1. Performance test results of each embodiment and comparative example. Example 1 2.5 58 1650 5200 19.5 88 Example 2 4.0 45 1500 4700 17.0 82 Example 3 3.2 63 1380 4250 20.2 85 Example 4 2.0 75 1200 3600 22.0 90 Comparative Example 1 18 22 980 2100 11.5 60 Comparative Example 2 3.0 55 1020 2800 16.0 42 Comparative Example 3 2.8 57 1600 4100 12.8 48 Comparative Example 4 1.5 8 760 1900 24.0 65 Comparative Example 5 6.0 24 1120 2600 13.6 58 As can be seen from the comparison of the test results of Example 1 and Comparative Example 1 in Table 1, omitting the gas-phase induced phase separation step leads to a weakening of the pore size gradient in the thickness direction, a reduction in the pore size difference on both sides of the membrane, and an inconspicuous asymmetric structure connecting the pore throats; the lack of a gas phase stage results in preferential water absorption and solvent evaporation on the surface, a more uniform distribution of polymer-rich and polymer-poor phases, and a decrease in capillary resistance when liquid water enters the membrane, thus reducing the water vapor permeability under hydrostatic pressure and high humidity conditions; As can be seen from the comparison of the test results of Example 1 and Comparative Example 2 in Table 1, omitting the second humidity-sensitive network leads to a decrease in the humidity response amplitude of water vapor transmission rate and a decrease in the mechanical recovery rate after repair. After the polyethylene glycol methyl ether acrylate network is missing, the hydrophilic phase that can adsorb water and generate controllable swelling in the pore wall is reduced, the ability of the pore throat size to regulate humidity changes is weakened, and at the same time, the lack of the second network inside the pore wall to supplement the chain segments on both sides of the crack reduces the degree of structural reconstruction in the damaged area. As can be seen from the comparison of the test results of Example 1 and Comparative Example 3 in Table 1, after replacing the dynamic disulfide crosslinking agent with conventional non-dynamic crosslinking components, the tensile strength recovery rate and hydrostatic pressure retention rate decreased; the membrane no longer has the dynamic covalent connection of disulfide bond exchange and mercapto group participation in recombination, and it is difficult to reconnect through reversible bond exchange after microcracks are formed, resulting in insufficient recovery of the continuity of the damaged area, thereby weakening the recovery ability of mechanical properties and liquid water barrier properties; As can be seen from the comparison of the test results of Example 1 and Comparative Example 4 in Table 1, after omitting the porogen, the membrane pore size decreases and the pore structure distribution tends to be denser, resulting in a decrease in water vapor permeability. The volume position occupied by the porogen during phase separation and washing originally helps to form pores and pore connectivity. After its absence, the proportion of polymer-rich phase increases, the pore walls thicken, and the diffusion channels decrease, thus reducing the air permeability. At the same time, the densification of the pore structure increases the hydrostatic pressure, but the air permeability decreases. As can be seen from the comparison of the test results of Example 1 and Comparative Example 5 in Table 1, after replacing the coagulation bath with pure water instead of the water and isopropanol mixture, the pore size gradient and pore throat size changed, and the water vapor permeability and hydrostatic pressure both decreased. After the coagulation bath composition changed, the solvent and non-solvent exchange rate lost its original regulation, the phase separation rate difference in the film thickness direction was weakened, and the resulting pore connectivity and asymmetric pore structure were insufficient, resulting in a decrease in the overall performance of liquid water barrier and water vapor transport. The above test results, including hydrostatic pressure, water vapor transmission rate, and tensile strength recovery rate, indicate that the hydrophobic regulating monomer, dynamic disulfide bond structure, and second humidity-sensitive network in the first network work together to reduce the impact of pore wall collapse, chain segment breakage, and interface defect expansion on air permeability and waterproof performance during aging, thereby enabling the material to maintain high comprehensive performance under damage and deformation conditions.

[0025] The above are merely specific embodiments of the present invention and are not intended to limit the present invention in any other way. Any person skilled in the art may make changes or modifications to the above-disclosed technical content to create equivalent embodiments for application in other fields. However, any conventional modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the technical solution of the present invention shall still fall within the protection scope of the technical solution of the present invention.

Claims

1. A weather-resistant and breathable composite material based on a microporous membrane, comprising a microporous membrane having a gradient interconnected microporous structure, characterized in that, The pore walls of the microporous membrane include a first cross-linked polymer network, a second cross-linked polymer network interpenetrating in the first cross-linked polymer network, and a dynamic disulfide bond structure distributed in the first cross-linked polymer network; The first crosslinked polymer network is formed by polymerization of N-isopropylacrylamide, a hydrophobic modifier monomer, and N,N-bisacryloylcysteine, wherein the hydrophobic modifier monomer is selected from one or more of octadecyl methacrylate, perfluorohexyl ethyl acrylate, and perfluorobutyl ethyl acrylate; The second crosslinked polymer network is formed by polymerizing polyethylene glycol methyl ether acrylate and a second network crosslinking agent, wherein the second network crosslinking agent is selected from one or more of polyethylene glycol diacrylate, polyethylene glycol dimethacrylate and polypropylene glycol diacrylate; the average pore size on the substrate contact side of the gradient interconnected microporous structure is 20-100 μm, and the average pore size on the gas phase contact side is 1-10 μm.

2. The weather-resistant and breathable composite material based on a microporous membrane according to claim 1, characterized in that, Based on a total of 100 moles of polymerizable double-bonded monomers, the reaction components of the first and second crosslinked polymer networks include: 60-80 moles of N-isopropylacrylamide, 3-15 moles of hydrophobic regulating monomer, 2-8 moles of N,N-bisacryloylcysteine, 10-30 moles of polyethylene glycol methyl ether acrylate, and 1-8 moles of the second network crosslinking agent.

3. The weather-resistant and breathable composite material based on a microporous membrane according to claim 1, characterized in that, The number average molecular weight of the polyethylene glycol methyl ether acrylate is 300-1000; the amount of the second network crosslinking agent is 2-8% of the molar number of polyethylene glycol methyl ether acrylate.

4. The weather-resistant and breathable composite material based on a microporous membrane according to claim 1, characterized in that, The first crosslinked polymer network also includes a sulfur-containing auxiliary monomer, which is selected from one or more of 2-mercaptoethyl acrylate and 2-mercaptoethyl methacrylate, and is used in an amount of 0.2-3 moles of the total number of polymerizable double bond monomers.

5. The weather-resistant and breathable composite material based on a microporous membrane according to claim 1, characterized in that, The first crosslinked polymer network further includes 1′-(2-acryloyloxyethyl)-3′,3′-dimethyl-6-nitrospiro[benzopyran-2,2′-indole] or 1′-(2-methacryloyloxyethyl)-3′,3′-dimethyl-6-nitrospiro[benzopyran-2,2′-indole], wherein the amount of 1′-(2-acryloyloxyethyl)-3′,3′-dimethyl-6-nitrospiro[benzopyran-2,2′-indole] or 1′-(2-methacryloyloxyethyl)-3′,3′-dimethyl-6-nitrospiro[benzopyran-2,2′-indole] is 0.05-1 molar part of the total molar number of all polymerizable double-bonded monomers.

6. The weather-resistant and breathable composite material based on a microporous membrane according to claim 1, characterized in that, The microporous membrane has a pore structure of conical pores, truncated conical pores, funnel-shaped pores, gradient throat structures, or combinations thereof; the average pore diameter on the substrate contact side is 30-80 μm, and the average pore diameter on the gas phase contact side is 2-8 μm.

7. The weather-resistant and breathable composite material based on a microporous membrane according to claim 1, characterized in that, The microporous membrane also includes a porogen selected from one or more of polyvinylpyrrolidone, polyethylene glycol, polyvinyl alcohol, and polyacrylic acid; the amount of the porogen is 5-30 wt% based on the total mass of polymerizable monomers in the first crosslinked polymer network.

8. The weather-resistant and breathable composite material based on a microporous membrane according to claim 7, characterized in that, The pore-forming agent is polyvinylpyrrolidone, and the weight-average molecular weight of the polyvinylpyrrolidone is 10,000-100,000; the mass ratio of the first crosslinked polymer network to the second crosslinked polymer network is 75:25 to 95:

5.

9. The weather-resistant and breathable composite material based on a microporous membrane according to claim 1, characterized in that, The first cross-linked polymer network and the second cross-linked polymer network form an interpenetrating structure through one or more of the following: covalent bonding, segment entanglement, hydrogen bonding, and polar interaction.